Dynamic Programming and Hamilton–Jacobi–Bellman Equations on Time Scales - Yingjun Zhu; Guangyan Jia (Complexity)
Bellman optimality principle for the stochastic dynamic system on time scales is derived, which includes the continuous time and discrete time as special cases. At the same time, the Hamilton–Jacobi–Bellman (HJB) equation on time scales is obtained. Finally, an example is employed to illustrate our main results.